Liminalitas Dakwah dalam Event Keagamaan Urban - Dede Irawan; Dudy Imanuddin Effendi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study examines how urban da’wah events shape religious experience through ritual processes infused with liminal atmospheres. The study focuses on Bandung as a social landscape that is both creative and deeply religious, where various religious events are organized by communities, mosque administrators, and event organizers. Using a phenomenological approach through in-depth interviews and observation, the research finds that da’wah events function not only as arenas of religious communication but also develop into episodic rituals. Participants step away from their daily routines, enter an in-between space filled with symbols and collective energy, and return to everyday life carrying renewed spiritual meaning. This process illustrates how urban da’wah adopts a ritual structure that binds identity, fosters communitas, and links religious expression with the cultural dynamics of the city.